Differences in Leadership Preferences and Levels of Narcissism Across Generations in the South African Workplace: An Initial Investigation - Hardenberg, Nastassja (Department of Psychology, 2024)
This study examined differences in leadership preferences and narcissism across three generations (Generations X, Y and Z). Based on most of the extant literature, both academic and popular, the expectation was that there would be significant differences across generations in their leadership preferences and levels of narcissism. A cross-sectional research design using an online survey obtained 230 responses (N = 230). Contrary to expectations, the research propositions were not supported; there were no significant differences across the generations on neither leadership preferences nor levels of narcissism. These unexpected findings are discussed with reference to recent research, aiming to inform organisational practices and generate dialogue for effectively managing generational diversity within organisations. Keywords: Leadership, Generational Diversity, Narcissism, Generation X, Generation Y, Generation Z, Multigenerational Workforce, South African Workplace